Antimicrobial and anti-biofilm activities of chlorogenic acid grafted chitosan against Staphylococcus aureus. (December 2022) - Yang, Xin; Lan, Weiqing; Xie, Jing
Abstract: In this work, Chitosan-grafted-chlorogenic acid (CS-g-CA) was prepared by the carbodiimide method. The purpose of this study was to investigate the antibacterial and anti-biofilm activity of CS-g-CA against Staphylococcus aureus ( S. aureus ). The minimum inhibitory concentration (MIC) of CS-g-CA against S. aureus was identified as 0.625 mg/mL. S. aureus treated with 1/2 × MIC of CS-g-CA had a longer logarithmic growth phase than that of the CK group, while 1 × MIC and 2 × MIC inhibited the growth of bacteria. The damaging effect of CS-g-CA on bacterial cells was analyzed by measuring the activity of cellular antioxidant enzymes (Catalase (CAT) and Glutathione peroxidase (GSH-Px)) and intracellular enzymes (alkaline phosphatase (AKPase) and adenosine triphosphatase (ATPase)). The results of DNA gel electrophoresis illustrated that CS-g-CA disrupted the normal metabolism of bacteria. Scanning electron microscopy (SEM) results showed that S. aureus shrank and died under CS-g-CA treatment. 1 × MIC of CS-g-CA can significantly inhibit the formation of biofilms, and 1/2 × MIC of CS-g-CA control the swimming speed of S. aureus . In addition, 77.53% mature biofilm and 60.62% extracellular polysaccharide (EPS) in the mature biofilm of S. aureus were eradicated by CS-g-CA at 2 × MIC. Confocal laser scanning microscopy (CLSM) observation further confirmed these results. Therefore, CS-g-CA was an antimicrobial and antibiofilm agent to control S. aureus, which can effectively controlling the growth of S. aureus in food, thereby preventing the occurrence of food-borne diseases. Graphical abstract: Image 1 Highlights: CS-g-CA showed antibacterial effect against Staphylococcus aureus. CS-g-CA inhibited Staphylococcus aureus growth by a membrane damage mechanism. CS-g-CA inhibited the motility and biofilm formation of Staphylococcus aureus. CS-g-CA is potential for planktonic Staphylococcus aureus and the biofilms control.